An Analysis of Illocutionary Acts Used by The Main Character in The Script of The Lion King Movie (1994) - Riskiyah, Putri; Marlina, Leni (Universitas Negeri Padang, 2021)
The illocutionary acts are the acts of doing something. When someone said something, it certainly has a meaning of what he/she said. Illocutionary acts can be seen in the movie because there are so many utterances that contain illocutionary acts which uttered by the movie characters. The Lion King (1994)one of the movies that have many illocutionary acts inside. This study aims to find out what are types of illocutionary acts used by the main character in the script of “The Lion King” movie (1994). This study also aims to find out what are types that dominantly used by the main character in the script of the Lion King movie (1994). This study used descriptive qualitative method. The data was taken from Simba utterances in the movie script. The data were analyzed based on Searle’s theory (1997) and classifying them into five types of illocutionary acts. They are representative, directive, commissive, expressive and declarative. The result of this study shown that The Lion King movie script contained all types of illocutionary acts that were uttered by the main character “Simba.” Representative 85 data or 65,3%, directive 39 data or 30%, commissive 3 data or 2,3%, expressive 2 data or 1,6%, and the last is declarative 1 data or 0,8%. Based on these result, representative was the dominant used by main character in the movie about 65,3% and declarative was the least appeared about 0,8%. It means The Lion King movie’s writer makes the main character of “Simba” use a lot of representative in order to inform or state something.